ANALISIS PLAGIARISME DALAM PENULISAN SKRIPSI MAHASISWA PROGRAM STUDI S1 PENDIDIKAN EKONOMI PEMBANGUNAN TAHUN 2010 -2014 UNIVERSITAS NEGERI MALANG - Pramita Lidya Yanuarista; Hari Wahyono; Dwi Wulandari (Universitas Negeri Malang, 2015)
In higher education, especially at S-1, students are trained to produce a scientific paper called thesis. Thesis is a scientific work created by the students as a graduation requirement in education S-1 which contains a philosophical objective of the study to a problem along with a review of the analysis based on specific research methodology used to solve these problems by The theoretical and accountable authenticity. But in writing a scientific work are still many students who committed plagiarism. This study used a qualitative descriptive approach to research that is naturalistic. Source of data in this research is secondary data in the form of student thesis S1 Economic Education Development 2010 to 2014. This research included in the research literature. Analysis of the data in this literature review is content analysis, which is a form of analysis that is used to provide a picture of a form of the object, which aims to describe the forms of plagiarism and layout arrangement acts of plagiarism in student thesis economic education development.